Integrated controls on the labile biogenic silica distribution in a muddy land–shelf continuum - Yunji Kim; Hoi Soo Jung; Jeongwon Kang; In Kwon Um; Seok Jang; Byung-cheol Kum (Regional Studies in Marine Science, 2026)

Polymer type drives successional structural and functional organization of plastisphere microbial networks - Kyu-Young Shim; In-Cheol Yeo; Euihyeon Lee; Hyun-Jung Kim; Kang Eun Kim; Jiezhang Mo; Youn-Jung Kim; Chang-Bum Jeong (Marine Environmental Research, 2026)

Multispecies toxicity evaluation of extractable chemicals from commercial biodegradable plastic products - Soyeon An; Hwicheol Shin; In-Cheol Yeo; Chang-Bum Jeong; Dong-Ku Kang (Journal of Hazardous Materials, 2026)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Development of high-performance organic photodetectors by understanding origin of dark current density with synthesis of photoconductive polymers - WonJo Jeong; Jinhyeon Kang; Dongchan Lee; Cheol Shin; Hyungju Ahn; Chan So; Jong Ho Won; Dae Sung Chung; Shinuk Cho; In Hwan Jung (Chemical Engineering Journal, 2023)

Coinfection with porcine epidemic diarrhea virus and Clostridium perfringens type A enhances disease severity in weaned pigs - Duri Lee; Guehwan Jang; Kyeng-Cheol Min; Inn Hong Lee; Hokeun Won; In-Joong Yoon; Sang Chul Kang; Changhee Lee (Archives of Virology, 2023)

Deletion of pentad residues in the N-terminal domain of spike protein attenuates porcine epidemic diarrhea virus in piglets - Guehwan Jang; Kyeng-Cheol Min; Inn Hong Lee; Hokeun Won; In-Joong Yoon; Sang Chul Kang; Changhee Lee (Veterinary Microbiology, 2023)

Effects of edible insect extracts on the antioxidant, physiochemical, and microbial properties of Tteokgalbi during refrigerated storage - Hae In Yong; Tae-Kyung Kim; Ji Yoon Cha; Jae Hoon Lee; Min-Cheol Kang; Samooel Jung; Yun-Sang Choi (Food Bioscience, 2023)

Peptides inhibiting angiotensin-I-converting enzyme: Isolation from flavourzyme hydrolysate of Protaetia brevitarsis larva protein and identification - Jae Hoon Lee; Tae-Kyung Kim; Hae In Yong; Ji Yoon Cha; Kyung-Mo Song; Hyo Geun Lee; Jun-Geon Je; Min-Cheol Kang; Yun-Sang Choi (Food Chemistry, 2023)

Poor outcomes of early recurrent post-transplant bloodstream infection in living-donor liver transplant recipients - Si-Ho Kim; Seok Jun Mun; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Gyu-Seong Choi; Jong Man Kim; Jae-Won Joh; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Risk factors for development and mortality of invasive pulmonary Aspergillosis in kidney transplantation recipients - Hyeri Seok; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Woo Seong Huh; Jae Berm Park; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Emergence of vancomycin-resistant Enterococcus faecium ST1421 lacking the pstS gene in Korea - Hye Mee Kim; Doo Ryeon Chung; Sun Young Cho; Kyungmin Huh; Cheol-In Kang; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Clinical factors influencing the performance of bacterial multiplex polymerase chain reaction in patients with community-onset pneumonia - Ga Eun Park; Kyong Ran Peck; Jae-Hoon Ko; Cheol-In Kang; Sun Young Cho; Doo Ryeon Chung; Nam Yong Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Clinical effectiveness of oral antimicrobial therapy for acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Kyoung Ree Lim; Hyunju Lee; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Evaluating the optimal dose of teicoplanin with therapeutic drug monitoring: not too high for adverse event, not too low for treatment efficacy - Si-Ho Kim; Cheol-In Kang; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Soo-Youn Lee; Yae-Jean Kim; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Molecular Identification and Expression Analysis of Carbonic Anhydrase VII in Pufferfish (Takifugu rubripes) - Kanij Rukshana Sumi; Soo Cheol Kim; Jewel Howlader; Md Rajib Sharker; Kap Seong Choi; Sang Ki Choi; Jong-In Park; Ill-Sup Nou; Kang Hee Kho (Ocean Science Journal, 2019)

Inappropriate empirical antibiotic therapy does not adversely affect the clinical outcomes of patients with acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Suhyun Oh; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Follow-up blood cultures add little value in the management of bacteremic urinary tract infections - HyeJin Shi; Cheol-In Kang; Sun Young Cho; Kyungmin Huh; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Pathogenic significance of hemorrhagic pneumonia in hematologic malignancy patients with Stenotrophomonas maltophilia bacteremia: clinical and microbiological analysis - Si-Ho Kim; Min Kyeong Cha; Cheol-In Kang; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Factors affecting the public awareness and behavior on antibiotic use - Kyungmin Huh; Doo Ryeon Chung; So Hyun Kim; Sun Young Cho; Young Eun Ha; Cheol-In Kang; Kyong Ran Peck; Jae-Hoon Song (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

A discontinuity in the late Pleistocene alluvial deposits, Hwacheon‐ri, Gyeongju, Korea: Occurrences and paleoenvironmental implication - Hoil Lee; In Sung Paik; Hyun Joo Kim; Hee‐Cheol Kang; Won Gyeong Seol; Jin‐Young Lee (Island Arc, 2018)
A sedimentary discontinuity is present in the late Pleistocene alluvial deposits exposed along the cliff in stream side, Gyeongju, Korea. Sedimentological study, Optically Stimulated Luminescence (OSL) age dating, and X‐ray diffraction (XRD), and X‐ray fluorescence spectrometer (XRF) analyses were conducted in order to interpret the origin of the discontinuity surface. Based on the sedimentological study, these deposits can be divided into three distinct stages, in ascending order: (Stage 1) development of a braided stream flowing from south to north and deposition by debris flows from the mountain aside the stream during and/or after deposition of the braided stream; (Stage 2) deposition by intermittent events during a state of stagnation after the abandonment or migration of the previously existed braided stream; and (Stage 3) deposition of gravels from debris flows from the mountain aside the stream. Hornfelsic gravels are common in Stage 1, whereas andesitic gravels are predominant in Stage 3, suggesting the provenance change from Stage 1 to Stage 3. The discontinuity surface is laterally extensive and marked by a distinct carbonaceous dark grey horizon between Stage 2 and Stage 3. It is characteristic that rootlets mineralized by vivianite are present, and iron‐oxide crusts are cutting across irregularly below the discontinuity surface. It is thus interpreted that the shift of depositional environment from an alluvial plain (Stage 2) (125 ka) to an alluvial fan (Stage 3) (94–55 ka) was an alluvial response to sea level change from the interglacial to the glacial. The development of iron‐oxide crusts and diagenetic vivianite in the discontinuity surface suggests humid condition persisted during the paleoclimatic shift from the last interglacial to the last glacial stages.

2-(4-{2-[(phenylthio)acetyl]carbonohydrazonoyl}phenoxy)acetamide as a new lead compound for management of allergic rhinitis - Hee-Yun Kim; Sun-Young Nam; Jae-Bum Jang; Youngjin Choi; In-Cheol Kang; Hyung-Min Kim; Hyun-Ja Jeong (Inflammation Research, 2016)

Inhibition effect of phenyl compounds from the Oryza sativa roots on melanin production in murine B16-F10 melanoma cells - Jin-Gyeong Cho; Jeongran Huh; Rak-Hun Jeong; Byeong-Ju Cha; Sabina Shrestha; Dong-Geol Lee; Hee-Cheol Kang; Ji-Young Kim; Nam-In Baek (Natural Product Research, 2015)

Flavonoids from Lindera glauca Blume as low-density lipoprotein oxidation inhibitors - Gyu-Won Huh; Ji-Hae Park; Ji-Hyun Kang; Tae-Sook Jeong; Hee Cheol Kang; Nam-In Baek (Natural Product Research, 2014)

Occurrences and origins of soft-sediment deformation structures in the late Pleistocene marine terrace deposits of the southeastern coast of Korea - Ho IL Lee; In Sung Paik; Hee Cheol Kang; Jong-Hwa Chun (Geosciences Journal, 2014)

Triterpenoids from Fragaria ananassa calyx and their inhibitory effects on melanogenesis in B16-F10 mouse melanoma cells - Na-Young Song; Jin-Gyeong Cho; Dongmoon Im; Dae-Young Lee; Qian Wu; Woo-Duck Seo; Hee Cheol Kang; Youn-Hyung Lee; Nam-In Baek (Natural Product Research, 2013)

Selenium Significantly Inhibits Adipocyte Hypertrophy and Abdominal Fat Accumulation in OLETF Rats via Induction of Fatty Acid β-Oxidation - Ji Eun Kim; Sun Il Choi; Hye Ryun Lee; In Sik Hwang; Young Ju Lee; Beum Soo An; Sang Hak Lee; Hak Jin Kim; Byeong Cheol Kang; Dae Youn Hwang (Biological Trace Element Research, 2012)

QTL analysis of back fat thickness and carcass pH in an F2 intercross between Landrace and Korean native pigs - Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; Taeyoung Kang; Jun Heon Lee; Hee-Bok Park; In-Cheol Cho (Molecular Biology Reports, 2012)

Cd2+ binds to Atx1 and affects the physical interaction between Atx1 and Ccc2 in Saccharomyces cerevisiae - Dong-Hyuk Heo; In-Joon Baek; Hyun-Jun Kang; Ji-Hyun Kim; Miwha Chang; Chang-Min Kang; Cheol-Won Yun (Biotechnology Letters, 2012)

Anti-angiogenic effects of the water extract of HangAmDan (WEHAD), a Korean traditional medicine - Ji-Young Bang; Kyung-Soon Kim; Eung-Yoon Kim; Hwa-Seung Yoo; Yeon-Weol Lee; Chong-Kwan Cho; YoungJin Choi; Hyun-Ja Jeong; In-Cheol Kang (Science China Life Sciences, 2011)

Nematicidal Activity of a Nonpathogenic Biocontrol Bacterium, Pseudomonas chlororaphis O6 - Jang Hoon Lee; Kyung Cheol Ma; Sug Ju Ko; Beom Ryong Kang; In Seon Kim; Young Cheol Kim (Current Microbiology, 2011)

Soft‐sediment deformation structures in Cretaceous non‐marine deposits of southeastern Gyeongsang Basin, Korea: Occurrences and origin - Hee‐Cheol Kang; In Sung Paik; Ho Il Lee; Jeong Eun Lee; Jong‐Hwa Chun (Island Arc, 2010)
A variety of soft‐sediment deformation structures formed during or shortly after deposition occurs in the Cretaceous Seongpori and Dadaepo Formations of the southeastern Gyeongsang Basin exposed along coastal areas of southeastern Korean Peninsula for 0.5–2 km. These are mostly present in a fluvial plain facies, with interbedded lacustrine deposits. In this study, the features of different kinds of soft‐sediment deformation structures have been interpreted on the basis of sedimentology of structure‐bearing deposits, comparison with normal sedimentary structures, timing and mechanism of deformation, and triggering mechanisms. The soft‐sediment deformation structures can be classified into four morphological groups: (i) load structures (load casts, ball‐and‐pillow structures); (ii) soft‐sediment intrusive structures (dish‐and‐pillars, clastic dykes, sills); (iii) ductile disturbed structures (convolute folds, slump structures); and (iv) brittle deformation structures (syndepositional faulting, dislocated breccia). The most probable triggering mechanisms resulting in these structures were seismic shocks. These interpretations are based on the following field observations: (i) location of the study area within tectonically active fault zone reactivated several times during the Cretaceous; (ii) deformation structures confined to single stratigraphic levels; (iii) lateral continuity and occurrences of various soft‐sediment deformation structures in the deformed level over large areas; (iv) absence of depositional slope to indicate gravity sliding or slumping; and (v) similarity to the structures produced experimentally. The soft‐sediment deformation structures in the study areas are thus interpreted to have been generated by seismic shocks with an estimated magnitude of M > 5, representing an intermittent record of the active tectonic and sedimentary processes during the development and evolution of two formations from the late Early Cretaceous to the Late Cretaceous.

Production of Indole-3-Acetic Acid in the Plant-Beneficial Strain Pseudomonas chlororaphis O6 Is Negatively Regulated by the Global Sensor Kinase GacS - Beom Ryong Kang; Kwang Yeol Yang; Baik Ho Cho; Tae Ho Han; In Seon Kim; Myung Chul Lee; Anne J. Anderson; Young Cheol Kim (Current Microbiology, 2006)

Comparative analysis of expressed sequence tags from Sesamum indicum and Arabidopsis thaliana developing seeds - Mi Chung Suh; Mi Jung Kim; Cheol-Goo Hur; Jung Myung Bae; Young In Park; Chung-Han Chung; Churl-Whan Kang; John B. Ohlrogge (Plant Molecular Biology, 2003)

Light- and electron-microscopic analysis of neuropeptide Y-immunoreactive amacrine cells in the guinea pig retina - Wha-Sun Kang; Min-Young Lim; Eun-Jin Lee; In-Beom Kim; Su-Ja Oh; Nicholas C. Brecha; Cheol-Beom Park; Myung-Hoon Chun (Cell and Tissue Research, 2001)